2012
DOI: 10.4081/jae.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitrogen content in buffalo manure and land application costs

Abstract: Buffalo (Bubalus bubalis) livestock for mozzarella cheese production plays a fundamental role in the economy of southern Italy. European and Italian regulations consider nitrogen content in buffalo manure to be the same as that of cattle manure. This study aimed to assess whether this assumption is true. The first aim of the study was to assess nitrogen content in buffalo manure. Samples were taken from 35 farms to analyse nitrogen and phosphorous concentration in the manure. Analysis confirmed a lower nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Urea 46% is provided as a top dressing. Considering an average N content of the liquid and solid manure of 1.96 g kg´1 [43], the amount of organic N applied yearly to the field is about 157 kg¨ha´1. During the silage corn cycle (dry season), sprinkler irrigation is provided weekly at an average rate of 50 mm.…”
Section: Site Description and Data Collectionmentioning
confidence: 99%
“…Urea 46% is provided as a top dressing. Considering an average N content of the liquid and solid manure of 1.96 g kg´1 [43], the amount of organic N applied yearly to the field is about 157 kg¨ha´1. During the silage corn cycle (dry season), sprinkler irrigation is provided weekly at an average rate of 50 mm.…”
Section: Site Description and Data Collectionmentioning
confidence: 99%
“…Recently, Pirlo et al (2014) observed that the environmental impact of dairy buffalo farms, expressed in terms of global warming, was 5.07 kg of CO 2 eq per 1 kg of normalised buffalo milk. Faugno et al (2012) found that buffalo manure has less nitrogen content than dairy cow manure. This difference may be attributed to the fact that dairy buffalo farms require energy inputs for the production and the purchase of raw materials similar to those of dairy cows, but lower outputs in terms of milk production can be obtained.…”
Section: Sustainability Of Dairy Buffalo Farmingmentioning
confidence: 99%
“…Another aspect of buffalo farming with a potentially high environmental impact is manure management. Faugno et al (2012) found that buffalo manure has less nitrogen content than dairy cow manure. In addition, they suggested that immediate incorporation is the best technique of manure spreading in terms of sustainability, albeit more expensive.…”
Section: Sustainability Of Dairy Buffalo Farmingmentioning
confidence: 99%